Postcomparison of [18F]‐fluorodeoxyglucose uptake in the brain after short‐term bright light exposure and no intervention. (30th March 2016) - Kohno, K.; Terao, T.; Hatano, K.; Kodama, K.; Makino, M.; Mizokami, Y.; Kamei, K.; Sakai, A.; Shirahama, M.; Hirakawa, H.; Kashino, G.; Matsumoto, S.; et al.
Abstract : Objective: Bright light therapy is widely used as the treatment of choice for seasonal affective disorder. Nonetheless, our understanding of the mechanisms of bright light is limited and it is important to investigate the mechanisms. The purpose of this study is to examine the hypothesis that bright light exposure may increase [ 18 F]‐fluorodeoxyglucose (FDG) uptake in olfactory bulb and/or hippocampus which may be associated neurogenesis in the human brain. Method: A randomized controlled trial comparing 5‐day bright light exposure + environmental light (bright light exposure group) with environmental light alone (no intervention group) was performed for 55 participants in a university hospital. The uptake of [ 18 F]FDG in olfactory bulb and hippocampus using FDG positron emission tomography was compared between two groups. Results: There was a significant increase of uptake in both right and left olfactory bulb for bright light exposure group vs. no intervention group. After adjustment of log‐transformed illuminance, there remained a significant increase of uptake in the right olfactory bulb. Conclusion: The present findings suggest a possibility that 5‐day bright light exposure may increase [ 18 F]FDG in the right olfactory bulb of the human brain, suggesting a possibility of neurogenesis. Further studies are warranted to directly confirm this possibility.